Anggrek Dataran Tinggi Habema di Distrik Nanggo Trikora, Jayawijaya, Papua - Verena Agustini; Supeni Sufaati; Suharno Suharno (Jurnal Biologi Papua, 2015)
New Guinea island is known as a home of tremendous collection of orchids. It is certainly in excess of 2500 species,  which is 10-13% of the world’s orchids. Some of those species are well described, but some remained unclear. Therefore many more await to be discovered. The aim of this research is to invent orchid’s species in Habema areas, Wamena. Explorative methods were used in this study. The results showed that there were 19 species consist of Dendrobium 11 species, Agrostophyllum 2 species, Glomera 2 species, Liparis 1 species and Bulbophyllum 1 species. Two species remained unidentified. Among them only five species are terrestrial, and eleven are epiphytes. The altitude is 2900-3700 m above sea levels; the rain fall is 1900 mm/year, humidity 86-95 %, with temperature of 14,5–24 oC.Key words: Orchids, exploration, highland, Habema